1970
DOI: 10.3758/bf03335543
|View full text |Cite
|
Sign up to set email alerts
|

Shock intensity effects in shuttle-box conditioning of guinea pigs

Abstract: Shock intensity effects in shuttle-box conditioning of gumea pigs Ibehavior in preliminary studies and the high shock was about the highest that could be administered repeatedly without injury to the Ss. Except for the shock intensity, the procedure was the same for all groups. The first session consisted of a 10-min adaptation period in the apparatus followed by 10 CS presentations.Following acc\imatization to the es, 50 delay conditioning trials, with a 10-sec es-ues interval and I-min intertrial intervaI, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Another way by which effective reinforcement may be increased is to provide a 48-hr, interval between shuttle-box sessions since fear of apparatus cues, but not fear of the discrete CS, shows forgetting in this length of time following conditioning (Goldman, 1969;McAllister & McAllister, 1968). Data reported by Webster and Rabedeau (1964) and by Rabedeau and Webster (1970), which show an improvement in shuttle-box avoidance learning in guinea pigs after a 48-hr, intersession interval, are consistent with this interpretation. In the latter study it was reported that the improvement in performance was greater in low-and medium-than in high-shock groups.…”
Section: Discussionmentioning
confidence: 80%
“…Another way by which effective reinforcement may be increased is to provide a 48-hr, interval between shuttle-box sessions since fear of apparatus cues, but not fear of the discrete CS, shows forgetting in this length of time following conditioning (Goldman, 1969;McAllister & McAllister, 1968). Data reported by Webster and Rabedeau (1964) and by Rabedeau and Webster (1970), which show an improvement in shuttle-box avoidance learning in guinea pigs after a 48-hr, intersession interval, are consistent with this interpretation. In the latter study it was reported that the improvement in performance was greater in low-and medium-than in high-shock groups.…”
Section: Discussionmentioning
confidence: 80%